Bioenergy and phytoremediation potential of Millettia pinnata - Kumar D.; Singh B.; Sharma Y.C. (My University, 2025)
Phytoremediation is currently being envisaged as an ecologically sustainable and economical decontamination technique for polluted sites. Phytoremediation being a slow process limits the utility of the site to an extent for other activities, and therefore valorisation of the biomass produced by some means is very important. Biomass-based energy (bioenergy) is increasingly gaining popularity as a relatively clean, renewable and carbon-neutral alternative to fossil fuels. Coupling phytoremediation with bioenergy production by using fast-growing hyperaccumulating species having bioenergy potential appears to be a rather attractive opportunity. Millettia pinnata is a hardy tree species with well-established bioenergy potential. The use of Millettia pinnata for simultaneous decontamination (of heavy metal contaminated sites) and bioenergy production has been discussed in this chapter. © Springer Nature Singapore Pte Ltd. 2017.